(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Ipomea batatas (I. batatas) commonly called Sweet potato are cultivated for food in more than 100 countries; the tuber is used as food without recourse to its toxic implications. Therefore, this research was designed to evaluate the effects of aqueous tuber extract of I. batatas on some organ weights, cardiac enzymes and lipid profile in Wistar rats. Twenty (20) male Wistar rats were divided into four (4) groups, each group consisting of five (5) animals. Group 1: was administered with distilled water while Groups 2, 3 and 4 were treated with 200,400, and 800 mg/ kg b.w doses of the extract of I. batatas respectively. The rats were sacrificed 24 h after treatment for twenty one (21) days. Serum obtained was used for analysis of the concentrations of creatine kinase (CK-MB), creatine kinase (CK), lactate dehydrogenase (LDH) and triglyceride, total cholesterol, low density lipoprotein, high density lipoprotein activity. Administered I. batatas extract at doses of 200, 400, and 800 mg kg-1 resulted significantly (P < 0.05) to increased mean weight of the body and organ weights (lung, liver and heart) of the rats respectively. There was a significant (P < 0.05) decrease in weight of testis but the effect on weight of seminal vesicle and epididymis was not significant (P > 0.05). There was reduction in the levels of triglyceride and total cholesterol, but this effect was not significant (P > 0.05). Administration of the extract at doses of 200, and 800 mg/kg b w significantly (P < 0.05) decreased the serum creatine kinase (CK-MB) and lactate dehydrogenase activity. These findings may probably suggest the cardio-protective effects of aqueous tuber extract of I. batatas at doses tested.